Simvastatin reduces NF-kB activity in peripheral mononuclear and in plaque cells of rabbit atheroma more markedly than lipid lowering diet - Hernández Presa, Miguel Angel; Ortego, Monica; Tunon, Jose; Martín Ventura, José Luis; Mas, Sebastian; Blanco Colio, Luis Miguel; Aparicio, César; Ortega, Luis; Gómez Gerique, Juan; Vivanco, Fernando; Egido, Jesús (My University, 2002)
Objective: To study whether simvastatin reduces inflammation in atherosclerosis beyond its hypolipidemic effects. Methods: Twenty-four rabbits with induced femoral injury and on an atherogenic diet were randomized to normolipidemic diet (n59), or to continue the atherogenic diet while receiving simvastatin 5 mg/kg/day (n59) or no treatment (n56) for 4 weeks. Results: As compared with no treatment, the normolipidemic diet significantly reduced lipid levels, while simvastatin produced nonsignificant reductions. In spite of this, NF-kB binding activity in peripheral mononuclear cells was reduced in the simvastatin group [2,95865,123 arbitrary units (a.u.)] as compared with no treatment (49,267620,084 a.u.; P,0.05) and normolipidemic groups (41,492615,876 a.u.; P,0.05) (electrophoretic mobility shift assay). NF-kB activity in the atherosclerotic lesions was also reduced by simvastatin as compared to 2 nontreated animals (4,10863,264 vs. 8,69662,305 nuclei/mm ; P,0.05), while the normolipidemic diet induced only a nonsignificant diminution (P.0.05) (Southwestern histochemistry). Similarly, simvastatin decreased macrophage infiltration (4.6612 vs. 19612% of area staining positive; P,0.05) and the expression of interleukin-8 (24612 vs. 63621%; P,0.05) and metalloproteinase-3 (1663 vs. 42628%; P,0.05) (immunohistochemistry), while the reduction achieved by normolipidemic diet in all these parameters was again nonsignificant (P.0.05). Conclusions: These findings suggest that simvastatin reduces inflammation in atherosclerotic plaques and in blood mononuclear cells more than expected for the lipid reduction achieved. ¿ 2002 European Society of Cardiology. Published by Elsevier Science B.V. All rights reserved. Keywords: Atherosclerosis; Cholesterol; Gene expression; Infection/inflammation; Macrophages; Statins